2013
DOI: 10.1371/journal.pone.0080314
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signature of Normal Cell-of-Origin Predicts Ovarian Tumor Outcomes

Abstract: The potential role of the cell-of-origin in determining the tumor phenotype has been raised, but not adequately examined. We hypothesized that distinct cells-of-origin may play a role in determining ovarian tumor phenotype and outcome. Here we describe a new cell culture medium for in vitro culture of paired normal human ovarian (OV) and fallopian tube (FT) epithelial cells from donors without cancer. While these cells have been cultured individually for short periods of time, to our knowledge this is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 59 publications
5
54
0
Order By: Relevance
“…These experiments identified a broad correlation between high HDAC7 protein expression with a variety of well-established CSC markers (Figure 3e, Supplementary Figure 10d). These results were also confirmed in tumour cells freshly isolated from seven primary human ovarian and breast cancers, 30 and in formalin-fixed paraffin-embedded sections of primary human breast cancer tissues (Supplementary Figure 11). In sum, we observed a correlation between eight CSC markers and high HDAC7 protein expression in seven cell lines and seven primary tumours using IF staining.…”
Section: Resultssupporting
confidence: 60%
“…These experiments identified a broad correlation between high HDAC7 protein expression with a variety of well-established CSC markers (Figure 3e, Supplementary Figure 10d). These results were also confirmed in tumour cells freshly isolated from seven primary human ovarian and breast cancers, 30 and in formalin-fixed paraffin-embedded sections of primary human breast cancer tissues (Supplementary Figure 11). In sum, we observed a correlation between eight CSC markers and high HDAC7 protein expression in seven cell lines and seven primary tumours using IF staining.…”
Section: Resultssupporting
confidence: 60%
“…For example, we previously demonstrated that while some normal cell types gave rise to highly tumorigenic and metastatic adenocarcinomas, other breast cell types that were isolated from the same patient and transformed with identical oncogenes gave rise to cells that were morphologically distinct, weakly tumorigenic, and nonmetastatic (16,(47)(48)(49). Others have also suggested that the same oncogenes can have vastly different phenotypic consequences depending on the cell of origin (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Primary fallopian tube secretory epithelial cells (FTECs) were isolated61 and cultured62 as previously described.…”
Section: Methodsmentioning
confidence: 99%